DETERMINANTS OF SUCCESSFUL IMPLEMENTATION OF LOCAL GOVERNMENT INFORMATION SYSTEMS: THE ROLE OF HUMAN RESOURCE COMPETENCY, GOVERNANCE, ORGANIZATIONAL INERTIA AS MODERATING VARIABLES - Nurhidayah, Nurhidayah; Masdar, Rahma; Usman, Rudy; Masruddin, Masruddin; Din, Muhammad (Jurnal Aplikasi Akuntansi, 2026)
In addition to analyzing the impact of governance and human resource competencies on the effective deployment of information technologies for local government, this study also looks at organizational Inertia as a moderating factor that may amplify or diminish these effects. This study offers novelty by positioning Organizational Inertia as a moderating variable, a factor that has received limited attention in prior SIPD implementation studies. Saturated sampling techniques were employed to collect primary data from 76 employees of the Central Sulawesi Provincial Financial and Asset Management Agency involved in the implementation of the Local Government Information System. The study took a quantitative approach. WarpPLS 8.0 was used to analyze the data using Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings demonstrated that there was no discernible impact of human resource competency. On the contrary, the success of system adoption is significantly impacted by Governance. Organizational Inertia, a moderating variable, strengthened the influence between independent and dependent variables. These results demonstrate that improving Governance is essential to the effective deployment of information technologies.